Dependency of effective modulus of polycrystalline aggregates on macro-geometric configuration - Fan, Hui (2013)
Polycrystalline aggregates are made in different macro-geometric configurations (line, thin film, bulk configurations etc.) for various engineering applications. Different mechanical behaviors and properties have been noticed among these configurations. In the present study, a finite element scheme with statistical consideration is employed to systematically investigate the effective modulus of polycrystalline copper in various geometric configurations. The numerical results show that the macro-scale geometric configuration is a key factor in determining the effective modulus of polycrystalline aggregates. The influence of microstructure on the effective modulus is examined by comparing the Voronoi model and uniform square grain model. The negligible discrepancy between the above two models indicates that the simple uniform model is feasible in simulating the real microstructure of polycrystalline aggregates with low and medium anisotropy.